Retaining Technology for Deep Foundation Pit Excavation Adjacent to High-Speed Railways Based on Deformation Control - Wang, Guohui; Chen, Wenhua; Cao, Liguo; Li, Youdong; Liu, Shuangchen; Yu, Junchao; Wang, Bingbing (Frontiers in Earth Science, 2021)
Considering the deep foundation pit of a car dumper room close to the Beijing–Baotou railway, the countermeasures of the foundation pit design are analyzed according to the surrounding environment and stratum conditions. Through Midas GTS software as well as field measured results, the construction effect on the adjacent railway subgrade is discussed. Therefore, the deformation characteristics of the foundation pit as well as the retaining structure, including the railway subgrade, caused by the excavation process, are revealed. The results show that the five-sided water-stop structure formed by cement piles around and at the bottom of the pit avoids the consolidation settlement of the adjacent railway subgrade caused by deep dewatering and also reduces the lateral displacement (i.e., in a horizontal direction) and the heave of the pit bottom. As a result, the lateral displacement near the railway side is larger than that of the retaining structure on the other side due to the subgrade on the pit side. The cross-lot bracing across the foundation pit will transfer the bias pressure of the subgrade to the retaining structure far away from the railway, while the transfer effect of the knee bracing is not obvious. The deformation of the railway subgrade and its evolution rate caused by the removal of internal bracing is significantly greater than the subgrade deformation and the change rate of deformation caused by excavation. The research results provide useful guidance for the deep foundation pit design.